2018
DOI: 10.33899/rjs.2018.159340
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation the Activity of 1,3,4-Thiadiazole Derivatives as Antibacterial Agent Against Uncommon Bacteria Causes of Urinary Tract Infections

Abstract: Schiff base compound 5-(benzylideneamino)-1,3,4-thiadiazole-2-thiol was prepared from condensation reaction of 2-amino-5-mercapto-1,3,4-thiadiazole with benzaldehyde. New Schiff bases react with copper (II), Ferric (III), Cobalt (II) and Zinc (II) to form four complexes. The Schiff base complexes were identification by using FTIR and UV-VIS. The antibacterial activity of complexes (Copper (II) LM 1 , Ferric (III) LM 2 , Cobalt (II) LM 3 and Zinc (II) LM 4 complexes) were studied against Kocuria kristinae, Allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…Resistance to broadspectrum cephalosporins (third and fourth generation) is achieved through diminishing permeability through the outer membrane, higher production of AmpC β-lactamase enzymes, acquisition of plasmids, or the combination of these factors together. The results of the present study are in accordance to those of a previous study [29], which showed the susceptibility of some Gram negative bacteria to 24 antibiotics. The authors found that most of the isolates were highly resistant to most of the antibiotics, which may be due to the production of β-lactamase.…”
Section: Susceptibility Of C Freundii To Antibioticssupporting
confidence: 92%
“…Resistance to broadspectrum cephalosporins (third and fourth generation) is achieved through diminishing permeability through the outer membrane, higher production of AmpC β-lactamase enzymes, acquisition of plasmids, or the combination of these factors together. The results of the present study are in accordance to those of a previous study [29], which showed the susceptibility of some Gram negative bacteria to 24 antibiotics. The authors found that most of the isolates were highly resistant to most of the antibiotics, which may be due to the production of β-lactamase.…”
Section: Susceptibility Of C Freundii To Antibioticssupporting
confidence: 92%